Pharmacological and nonpharmacological studies on coronavirus disease 2019: A mini-review of the recent evidence - Amir Hossein Alizadeh Bahmani; Mehdi Hoorang; Sheida Hosseini; Mehrnoosh Eskandari; Kiana Shayestehfard; Mahyar Shekoohi; Nazafarin Hatami-Mazinani; Saba Afifi; Ali Mohammad Sabzghabaee; Payam Peymani (Wolters Kluwer Medknow Publications, 2020)
Coronavirus 19 (COVID-19) is an extremely transmittable microbial infection that has emerged in Wuhan (China) in late 2019, leading to severe acute respiratory syndrome coronavirus 2 syndrome, and caused a pandemic all over the globe. This study is a systematic review of all 927 clinical trial studies performed worldwide from the beginning of the COVID-19 mysterious pandemic in China. These researches have registered in different databases. According to the best of our knowledge, China (74.82%), the United States (4.49%), and France (2.72%) have the most significant number of clinical trials, respectively. Clinical trials can be randomized or nonrandomized. Due to our results, 32.58% of studies were randomized, and 7.12% were not randomized. Most of the studies were open-labeled studies (22.44%), and double-blinded (4.42%) and quadruple blinded (2.48%) studies stand in second and third place regarding the number of trials, respectively. The direction and quantity of clinical trials attempted to identify a possible cure for COVID-19 demonstrates the depth of this crisis. As we are writing this article, a significant international endeavor will find a cure or vaccine for containing this devastating and mysterious disease.